Flexible Work – Right Solution or Fallacy - Jašarević, Senad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Flexibilization of labor is one of the most common ways to increase the efficiency and adaptability of the economy and companies in times of crisis and globalized economy. Flexibility of work can be internal, external, micro, macro, functional, numerical, financial. Ways of flexibilization can be quite diverse, ranging from deregulation of labor law regulations, through wider use of atypical forms of employment, flexible working time and work organisation, etc. Although labor flexibilization brings numerous benefits, it is also accompanied by many negative aspects. Flexibilization of labor may be harmful if it is carried out haphazardly and if it is not balanced with measures intended to preserve social security for workers during periods of change.